Assistance in nursing care for preparation for normal childbirth (Research, Society and Development, 2024)
The experience of becoming a mother is one of the most significant and anticipated events in a woman's life. Prenatal care should be a form of holistic and humanized support from the beginning of pregnancy. Nurses involved in facilitating natural childbirth should respect the woman's timing in the birthing process, avoiding unnecessary interventions, and recognizing the socio-cultural aspects of each pregnant woman. The study aimed to understand the practice of nurses in primary care in preparing for natural childbirth. The methodology used for the study was exploratory, descriptive, with a qualitative approach. The research began in August 2018, and data collection was carried out from April to May 2019, in the Family Health Strategy (FHS) in the municipality of Coreaú. It involved eleven nurses working in the FHS, who were subjected to a semi-structured interview. To understand natural childbirth as a physiological process that is minimally influenced by assisting professionals, it is necessary to ensure greater safety for the mother-child pair. However, deficiencies were identified in the assistance related to preparation, such as lack of knowledge about its benefits. The interviewed nurses showed extensive knowledge about preparing for natural childbirth, although it is still met with categorical apprehension by the pregnant women they assist. Nevertheless, they are increasingly finding ways to educate these mothers.